ACADEMIC WRITING A HANDBOOK FOR STUDENTS - BAILEY STEPHEN (NEW YORK ROUTLEDGE COMPANION WEBSITE, 2018)
The book you are referring to is most likely Academic Writing: A Handbook for International Students by Stephen Bailey. It is a very popular and comprehensive guide, especially for non-native English speakers transitioning to university-level writing in English.
Acedmic Writing
All Branches
Keywords: English